SIKAP MENTAL PETANI DALAM USAHA BIDANG PERTANIAN TANAMAN PANGAN DI DESA JIRENNE KABUPATEN LANNY JAYA PROPINSI PAPUA - Yigibalom, Yosia; Lumintang, Juliana; Paat, Cornelius J. (HOLISTIK, Journal Of Social and Culture, 2020)
Indonesia has a tropical climate that is a rainy and dry season in which it is widely used for irrigation and rain-farming activities. With these two seasons, farmers can improve their farms and adjust the plants or what kind of crops to be planted in the rainy or dry season. Jirenne Village of Lanny Jaya, Papua, has a natural resource that is still abundant because of its fertile soil condition. Food crops are often used as a source of livelihood of Jirenne villagers such as sweet potato, sago and banana plants that are used as a source of basic livelihood.The mental attitude of community farmers Jirenne Village does not have the ability in agriculture to process the foodstuffs intensively, this is because the community in this village is also still believe in the tradition in which planting must have adherence to customs.But if planting during the dry season, it is likely that crops will not be able to grow well. This belief is inherent in village society, making it difficult to change. The attitude of believing mystical things still affects the people of Jirenne village.Mutual and mutual help in farming communities to participate in helping their fellow communities in planting crops to utilize vacant land for farming.Keywords: farmer, agriculture, foodstuff